EFFECT OF ACUPUNCTURE IN HEART AURICULAR POINT IN TWO INDEXES OF DIGITAL VOLUME PULSE IN HEALTHY SUBJECTS - SERRANO-MORALES, MIGUEL MIZRAIM; MEJÍA-GONZÁLEZ, MARCIAL; CASTAÑEDA-RAMÍREZ, MOISÉS SALVADOR; RIVAS-VILCHIS, JOSÉ FEDERICO (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the study was to determine the changes in two indices derived from the digital volume pulse (DVP) elicited by acupuncture in auricular heart acupoint in healthy subjects. Methods: Eighteen healthy subjects aged 26.22±2.98 years (mean±standard deviation) were assigned to receive auricular acupuncture in auricular heart acupoint in the right ear. The DVP was recorded by photoplethysmography. RIDVP was determined by the relative amplitudes of systolic and diastolic components of the DVP and SIDVP, by the relative timing of these components. Auricular acupoint heart was stimulated by manual acupuncture. The RIDVP and SIDVP indices were calculated for basal and post-acupuncture conditions. Results: Both RIDVP (p=0.0375) and SIDVP (p=0.0063) were significantly decreased by acupuncture of the right auricular acupoint heart when comparing the pre- and post-acupuncture values. Conclusions: These results indicate that manual acupuncture of auricular acupoint heart produces acute effects on vascular physiology. RIDVP and SIDVP indices can be used to assess and demonstrate a vasodilatory activity of auricular acupoint heart.